NF-kappa B and Oct-2 synergize to activate the human 3' Igh hs4 enhancer in B cells - Sepulveda, Manuel A; Emelyanov, Alexander V; Birshtein, Barbara K (The Journal of immunology (1950), 2004)
In B cells, the Igh gene locus contains several DNase I-hypersensitive (hs) sites with enhancer activity. These include the 3' Igh enhancers, which are located downstream of the Calpha gene(s) in both mouse and human. In vivo experiments have implicated murine 3' enhancers, hs3B and/or hs4, in class switching and somatic hypermutation. We previously reported that murine hs4 was regulated by NF-kappaB, octamer binding proteins, and Pax5 (B cell-specific activator protein). In this study we report that human hs4 is regulated differently. EMSAs and Western analysis of normal B cells before and after stimulation with anti-IgM plus anti-CD40 showed the same complex binding pattern formed by NF-kappaB, Oct-1, and Oct-2 (but not by Pax5). A similar EMSA pattern was detected in mature human B cell lines (BL-2, Ramos, and HS-Sultan) and in diffuse large B cell lymphoma cell lines, although yin yang 1 protein (YY1) binding was also observed. We have confirmed the in vivo association of these transcription factors with hs4 in B cells by chromatin immunoprecipitation assays. The diffuse large B cell lymphoma cell lines had a distinctive slow-migrating complex containing YY1 associated with Rel-B. We have confirmed by endogenous coimmunoprecipitation an association of YY1 with Rel-B, but not with other NF-kappaB family members. Transient transfection assays showed robust hs4 enhancer activity in the mature B cell lines, which was dependent on synergistic interactions between NF-kappaB and octamer binding proteins. In addition, human hs4 enhancer activity required Oct-2 and correlated with expression of Oct coactivator from B cells (OCA-B).